Computational Evaluation of Intermolecular Interaction in Poly(Styrene-Maleic Acid)-Water Complexes Using Density Functional Theory - Daru Seto Bagus Anugrah; Laura Virdy Darmalim; Permono Adi Putro; Liana Dewi Nuratikah; Nurwarrohman Andre Sasongko; Parsaoran Siahaan; Adi Yulandi (Indonesian Journal of Chemistry, 2021)
The high application of Poly(styrene-maleic acid) (PSMA) in an aqueous environment, such as biomedical purposes, makes the interaction between PSMA and water molecules interesting to be investigated. This study evaluated the conformation, the hydrogen bond network, and the stabilities of all the possible intermolecular interactions between PSMA with water (PSMA−(H2O)n, n = 1–5). All calculations were executed using the density functional theory (DFT) method at B3LYP functional and the 6–311G** basis set. The energy interaction of PSMA–(H2O)5 complex was –56.66 kcal/mol, which is classified as high hydrogen bond interaction. The Highest Occupied Molecular Orbital (HOMO) – Lowest Unoccupied Molecular Orbital (LUMO) energy gap decreased with the rise in the number of H2O molecules, representing a more reactive complex. The strongest hydrogen bonding in PSMA–(H2O)5 wasformed through the interaction on O72···O17–H49 with stabilizing energy of 50.32 kcal/mol, that analyzed by natural bond orbital (NBO) theory. The quantum theory atoms in molecules (QTAIM) analysis showed that the hydrogen bonding (EHB) value on O72···O17–H49 was –14.95 kcal/mol. All computational data revealed that PSMA had moderate to high interaction with water molecules that indicated the water molecules were easily transported and kept in the PSMA matrix.